(untitled) (International Journal of Physiotherapy, 2025)
Background: A student life is full of challenges and opportunities. Academic stress, the use of modern-day gadgets such as smartphones and tablets, the modern lifestyle, and many other contributing factors can lead to difficulty in sleeping. Poor sleep has been associated with a lack of focus, concentration, psychological and psychosomatic issues. The impact of exercise on various sleep disorders and sleep attributes among a university student population is relatively limited. This study aims to investigate the effect of acute moderate-intensity aerobic exercise (AMIAE) on insomnia and daytime sleepiness among insomniac university students. Methods: 31 (67% females, 32.3% males) healthy sedentary undergraduate university students suffering from insomnia symptoms (Athens’ insomnia score) have participated in the study. A single bout of moderate intensity aerobic exercise with a duration of 30 minutes, excluding warm up and cool down, given at the intensity (determined by 40% to <60% of Target Heart Rate (THR)) on a treadmill has been used as an intervention strategy. Pre and post-scores of the Athens Insomnia Scale (AIS) and daytime sleepiness using the Epworth Sleepiness Scale (ESS) were measured before and after the exercise intervention. Results: Paired sample t-test has shown a significant reduction (p < 0.001) in the mean score of the Athens Insomnia Scale (AIS) from 8.74+/-2.54 before the exercise intervention to 5.55+/-4.27 after the exercise session. The Epworth Sleepiness Scale (ESS) also showed a significant decrease (p < 0.001) in mean score, from 8.52 ± 3.99 to 6.23 ± 4.30. Conclusion: This study demonstrates that acute moderate-intensity aerobic exercise (AMIAE) can enhance sleep among university students. These findings can serve as a reference and also motivate us to explore the role of exercise and physiotherapy techniques in the field of sleep medicine. Students are considered the future of tomorrow, and the inculcation of appropriate exercises guided by a physiotherapist at the grassroots level (including schools and higher education) is essential. It may help them to have sound sleep and stay healthy, which can have a substantial positive impact.